The Effect of Social Context on the Mind Perception of Robots. (November 2019) - Butler, Rebecca; Pruitt, Zoe; Wiese, Eva
As social robots are increasingly introduced into our everyday lives, an emphasis on improving the human-robot interaction (HRI), particularly through increased mind perception, is necessary. Substantial research has been conducted that demonstrates how manipulations to a robot's physical appearance or behavior increases mind perception, yet little has been done to examine the effects of the social environment. This study aims to identify the impact of social context on mind perception by comparing mind perception ratings assigned to robots viewed in a human context with those assigned to robots viewed in a robot context . Participants were assigned to one of the two contexts in which they viewed images of 5 control robots with either 15 humans or 15 robots and answered questions that measured the degree to which they ascribed mind to the agents. A t-test comparing the overall average mind ratings of the control robots between contexts showed a significant difference between the two, with the robots in the robot context having a higher average rating than those in the human context . This result demonstrates a need to consider the social context in which the HRI will take place when designing for the best interaction. Considering that most robots in the foreseeable future will be viewed in a human context, this result also calls for additional research on ways to further increase mind perception to combat the negative effect of the most likely social environment.